Are quitting-related cognitions and behaviours predicted by proximal responses to plain packaging with larger health warnings? Findings from a national cohort study with Australian adult smokers. (25th February 2015) - Brennan, Emily; Durkin, Sarah; Coomber, Kerri; Zacher, Meghan; Scollo, Michelle; Wakefield, Melanie
Abstract : Background: Implementation of tobacco plain packaging (PP) with larger graphic health warnings (GHWs) in Australia had positive effects on responses reflecting the specific objectives of the PP policy and on follow-up quitting-related cognitions and behaviours. The aim of this study was to examine predictive relationships between these proximal and distal outcomes. Methods: A nationally representative sample of Australian adult cigarette smokers completed a baseline survey and a 1-month follow-up survey within the first year of policy implementation (n(weighted)=3125). Logistic regression analyses tested whether baseline measures of cigarette appeal, GHW effectiveness, perceived harm and concern/enjoyment predicted each of seven follow-up measures of quitting-related cognitions and behaviours, adjusting for baseline levels of the outcome and covariates. Results: In multivariable models, we found consistent evidence that several baseline measures of GHW effectiveness positively and significantly predicted the likelihood that smokers at follow-up reported thinking about quitting at least daily, intending to quit, having a firm date to quit, stubbing out cigarettes prematurely, stopping oneself from smoking and having attempted to quit. Two of the quitting-related outcomes were also predicted by feeling more smoking-related concern than enjoyment. A smaller number of the appeal variables were prospectively associated with quitting-related outcomes, while believing that brands do not differ in harmfulness did not positively predict any outcomes. Conclusions: These findings provide an initial insight into the pathways through which PP with larger GHWs may lead to changes in smoking behaviour. Future research should examine whether the effects are conditional on individual demographic and smoking characteristics.